Risk Factors for Biochemical Recurrence After PSMA-PET-Guided Definitive Radiotherapy in Patients With De Novo Lymph Node-Positive Prostate Cancer - Spohn, Simon K.B.; Birkenmaier, Viktoria; Ruf, Juri; Mix, Michael; Sigle, August; Haehl, Erik; Adebahr, Sonja; Sprave, Tanja; Gkika, Eleni; Rühle, Alexander; Nicolay, Nils H.; Kirste, Simon; et al. (Frontiers in Oncology, 2022)
Introduction: National comprehensive cancer network recommends external beam radiotherapy (EBRT) combined with androgen deprivation therapy (ADT) for newly diagnosed node positive (cN1) prostate cancer (PCa) patients as the preferred treatment option. However, implementation of positron-emission-tomography targeting prostate-specific-membrane-antigen (PSMA-PET) in staging of primary PCa patients has significant impact on RT treatment concepts. This study aims to evaluate outcomes and its respective risk factors patients with PSMA-PET based cN1 and/or cM1a PCa receiving primary RT and ADT. Methods: 48 patients with cN0 and/or cM1a PCa staged by [18F]PSMA-1007- (n=19) or [68Ga]PSMA-11-PET (n=29) were retrospectively included. All patients received EBRT to the pelvis±boost to positive.nodes, followed by boost to the prostate. The impact of different PET-derived characteristics such as maximum-standard-uptake-value (SUVmax) and number of PET-positive lymph-nodes on biochemical-recurrence-free survival (BRFS) (Phoenix-criteria) and metastases-free-survival (MFS) was determined using Kaplan-Meier and Cox-proportional-hazard-regression-analyses. Results: Median follow up was 24 months. Median initial serum prostate-specific-antigen was 20.2 ng/ml (IQR 10.2 – 54.2). Most patients had cT stage ≥ 3 (63%) and ISUP grade ≥ 3 (85%). Median dose to the prostate, elective nodes and PET-positive nodes was 75Gy, 45 Gy and 55 Gy. 90% of patients received ADT with a median duration of 9 months (IQR 6-18). In univariate analysis, cM1a stage (p=0.03), number of >2 pelvic nodes (n=0.01), number of > 1 abdominal node (p=0.02) and SUVmax values ≥ median (8.1 g/ml for 68Ga-PSMA-11 and 7.9 g/ml for 18F-PSMA-1007) extracted from lymph-nodes were significantly associated with unfavorable BRFS, classical clinicopathological features were not. Number of >2 pelvic nodes (n=0.03), number of > 1 abdominal node (p=0.03) and SUVmax values ≥ median extracted from lymph nodes were associated with unfavorable MFS. In multivariate analysis number of > 2 pelvic lymph nodes was significantly associated with unfavorable BRFS (HR 5.2, p=0.01) and SUVmax values ≥ median extracted from lymph nodes with unfavorable MFS (HR 6.3, p=0.02). Conclusion: More than 2 PET-positive pelvic lymph nodes are associated with unfavorable BRFS and high SUVmax values with unfavorable MFS. Thus, the number of PET-positive lymph nodes and the SUVmax value might be relevant prognosticators to identify patients with favorable outcomes.